Genomic Diversity of the tet(X)-Positive Myroides Species - Chong Chen; Taotao Wu; Jing Liu; Yilin Lv (Microorganisms, 2025)
The rapid spread of tet(X) genes capable of inactivating tigecycline represents a critical challenge to global public health. This study aims to explore the distribution, genetic diversity, and transferability of tet(X) genes in Myroides, a genus of Gram-negative bacteria increasingly implicated in multidrug-resistant (MDR) bacterial infections. From 2021 to 2024, 646 samples of chicken, sheep, soil, and water were randomly collected, yielding nine chicken-derived tet(X)-positive Myroides sp. strains in Shandong, China. All of them were MDR to tetracycline, ceftazidime, gentamicin, amikacin, colistin, ciprofloxacin, gatifloxacin, and trimethoprim-sulfamethoxazole, with elevated minimum inhibitory concentrations (MICs) for tigecycline, florfenicol, and macrolides, but exhibited susceptibility to meropenem (100%), ampicillin-sulbactam (66.7%), and cefotaxime (33.3%). A genomic analysis of the isolates and 86 public tet(X)-positive Myroides genomes revealed the widespread distribution of tet(X) and macrolide-inactivating estT genes across 12 Myroides species, including 7 novel species. Eight tet(X) and eight estT variants were identified, half of which were novel. The phylogenetic analysis highlighted interspecies transmission risks, with ISCR2-mediated transposons of tet(X6) and estT-2 across Myroides, Riemerella, Empedobacter, Providencia, Acinetobacter, and Proteus species. These findings illuminate the genomic diversity driving antibiotic resistance in understudied bacterial taxa, with implications for global One Health strategies.